Entrepreneurship and Self-Reliant Economy : A Hope for Success - Bargal, Hitendra; Patel, Vinod Kumar; Gupta, Prashant (AMC Indian Journal of Entrepreneurship, 2024)
Purpose : This study explored the role of entrepreneurship in achieving a self-reliant economy by analyzing the interplay between governmental policies, innovation, and resource utilization. Design/Methodology : A systematic literature review approach was adopted, incorporating secondary data to assess trends and impacts. Findings : The results indicated that targeted policies and skill development initiatives significantly enhanced entrepreneurial outcomes, particularly in rural areas. Practical Implications : Insights from this study guided policymakers, entrepreneurs, and educators in developing sustainable ecosystems for entrepreneurship. Originality/Value : This research contributed to the literature by addressing gaps in policy-driven entrepreneurial development and its impact on economic self-reliance.